Pertanggungjawaban Korporasi dalam Penyalahgunaan Data Pribadi oleh Debt collector Pinjaman Online; Analisis Teori Vicarious Liability - Mandala, Azi Fachri; Firmansyah, Hery (IAIN Langsa, 2025)
This study aims to analyze the form of corporate criminal liability in cases of personal data misuse by online loan debt collectors through the lens of vicarious liability theory. The research contributes by providing a theoretical foundation and legal argumentation to support regulatory efforts and law enforcement against data misuse practices in the digital financial sector. This article falls under qualitative library research. The methodology employed is normative legal analysis. The findings indicate that actions by debt collectors who misuse borrowers' personal data for corporate gain may result in criminal liability for the corporation, particularly when the company fails to prevent or supervise such conduct. The theory of vicarious liability reinforces the principle that corporations cannot escape responsibility for legal violations committed by individuals acting on their behalf or for their benefit.